PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN OPEN ENDED PADA MATERI RELASI DAN FUNGSI SISWA KELAS VIII SMP - Rahmadani Sukma Melati; Lucy Asri Purwasi; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to develop worksheets on relations and functions for class VIII students of SMPN 2 Lubuklinggau and to produce valid and practical student worksheets on relations and functions for class VIII students at SMPN 2 Lubuklinggau. This research is a development research with a 4-D (Four-D) development model. This model consists of 3 stages of development, namely the Define stage, Design stage, and Develop stage. The Define stage includes: a) initial analysis, b) student analysis, c) task analysis d) concept design, and e) formulate objectives. The process at the Design stage includes: a) format selection, and b) initial design. The process at the Develop stage includes: a) validation by experts followed by revisions, b) product trials. The product of this research is in the form of student worksheets on Relations and Functions with an open ended approach. The results showed that: (1) Validity showed that the developed student worksheets received a very valid category in the language feasibility component with an average score of 4.16, in the material feasibility component received a very valid category with an average score of 4, 00, while the media feasibility component gets a very valid predicate with an average score of 4.44. (2) the quality of student worksheets seen from the practicality aspect is included in the criteria of